The role of information technology in improving organizational performance A field study on insurance companies operating in the city of Lattakia - تفاحة حيدر; جميل عيسى; حيان بركات (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The research aims to determine the role of information technology in its dimensions (human resources, hardware and equipment, software and databases, networks) in improving organizational performance in private insurance companies operating in the city of Lattakia. Distributing a questionnaire to (60) employees working at the upper and middle management levels (section heads and administrative employees) in the companies under study. The number of questionnaires retrieved and valid for analysis and which were unloaded reached (51). The researchers also relied on the descriptive analytical approach of the most prominent statements in periodicals, scientific journals and books. The research showed a strong correlation between information technology in its dimensions and improving organizational performance in the companies under study. The researchers also made a set of recommendations, the most prominent of which were: the need to increase investment in the field of information technology in addition to conducting more training courses for human cadres and working to benefit from the capabilities of information technology in enhancing employee participation, which is positively reflected on improving organizational performance.